2017
DOI: 10.4028/www.scientific.net/ssp.262.48
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Population of Industrial Biooxidation Reactors

Abstract: Microbial population performing biooxidation of flotation concentrate of gold bearing sulfide ore containing pyrite, arsenopyrite, and pyrrhotite was studied using cultural and molecular biological (metagenomics sequencing of V3-V4 fragments of 16S rRNA gene) approaches. The biooxidation of the concentrate was conducted at temperatures from 38 to 42°C. Strains of Acidithiobacillus thiooxidans, Acidiphilium multivorum, Leptospirillum ferriphilum, Sulfobacillus thermotolerans, Ferroplasma acidarmanus, and Ferrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
(11 reference statements)
0
15
0
1
Order By: Relevance
“…The growth of chemomixotrophic F. acidiphilum was favored by the supernatant of chemolithoautotrophic L. ferriphilum, containing additional sources of the organic carbon (EPS and lysed cells) and vice versa, probably due to detoxification of the medium from organic compounds by mixotrophic F. acidiphilum and extracellular proteins of its "secretome" [58]. The study of the microbial community dynamics in various industrial processes of tank or heap biooxidation showed the dominance of the Ferroplasmaceae family members [59][60][61]. According to the results of our study, F. acidiphilum played a crucial role in the oxidation of sulfide minerals of the leach residue of the zinc concentrate by the mixture of microbial cultures.…”
Section: Microbialmentioning
confidence: 99%
“…The growth of chemomixotrophic F. acidiphilum was favored by the supernatant of chemolithoautotrophic L. ferriphilum, containing additional sources of the organic carbon (EPS and lysed cells) and vice versa, probably due to detoxification of the medium from organic compounds by mixotrophic F. acidiphilum and extracellular proteins of its "secretome" [58]. The study of the microbial community dynamics in various industrial processes of tank or heap biooxidation showed the dominance of the Ferroplasmaceae family members [59][60][61]. According to the results of our study, F. acidiphilum played a crucial role in the oxidation of sulfide minerals of the leach residue of the zinc concentrate by the mixture of microbial cultures.…”
Section: Microbialmentioning
confidence: 99%
“…The object of this research was an acidophilic bacterial strain isolated as a predominant sulfur oxidizer from a bioreactor during the processing of the gold-containing sulfidic concentrate at 38 °C [ 15 ]. Biotechnologies for tank biooxidation of sulfidic concentrates using sulfur- and iron-oxidizing acidophilic microorganisms were developed in the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…spp., Leptospirillum ( L. ) spp., Sulfobacillus ( Sb. ) spp., Ferroplasma ( F. ) spp., and some other microorganisms [ 15 , 17 , 18 , 19 , 20 , 21 , 22 ]. The Olympiada biooxidation plant is located in the Krasnoyarsk Krai (Siberia, Russia) and has been operated by Polyus Krasnoyarsk JSC since 2001.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sb. thermotolerans is continuously identified as the predominant bacterium in the biomining microbial communities during laboratory-scale and industrial processes of bioleaching/biooxidation of refractory gold ores [ 6 , 11 , 12 , 13 ]. This thermotolerant species possesses a versatile metabolism, which provides for its functioning under fluctuating conditions of natural environments and technological processes (changes in pH and temperature, pulp density, concentrations of heavy metals and metalloids, as well as the availability of energy substrates and oxygen or other electron acceptors to cells) [ 8 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%